The power of habit - Akin, Elva Veola (My University, 1905)
Introduction: Habit is second nature; yet who of us has ever stopped to think about it? When we repeat those words we should try to discover who it was in the first place that invented or revealed it in some manner. He must have possessed philosophical and psychological powers of no limited quantity. Habit is that which by use has become natural to us; nature is habit handed down by our ancestors, and ingrained bodily in the very structure of our brains, muscles, and nervous systems. It is well known that the children of juggler, rope-dancers, tumblers and acrobats can be much more easily trained and taught their father’s profession than any casual ordinary members of the general public. They are born, in fact, with quicker fingers, more supple limbs, nimbler toes, easier muscles than the vast mass of their fellow citizens. The constant practice of hand or foot has made a real difference at least in the very structure and fibres of their bodies; and this difference is transmitted to their children, so that the conjurer, like the poet, is to some extent born, not made. It is just the same with many arts and handicrafts
Citation: Akin, Elva Veola. The power of habit. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Habit's Result on Physical Body; Habit vs. Will; Habit's relation to Health and Disease; Theses